2007
DOI: 10.1111/j.1600-0625.2007.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of selectively expressed genes and antigens in CTCL

Abstract: The knowledge of tumor-associated antigens is required for most types of immunotherapy and can substantially facilitate diagnosis. To identify potential tumor-associated genes expressed in cutaneous T-cell lymphoma (CTCL), we used three complementary strategies: antigens which elicit a humoral immune response in CTCL patients were detected by serological analysis of a recombinant cDNA expression library. cDNAs differentially expressed in CTCL but not peripheral blood monocytes were identified by comparative cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 58 publications
0
28
0
Order By: Relevance
“…12 Tat-interacting protein of 110 kDa (TIP110), which was initially cloned from a human KG-1 myeloid cell line cDNA library, 13 is implicated in RNA metabolism and tumor-antigen presentation. [14][15][16][17] We demonstrated previously that TIP110 regulates the transcription of HIV-1 and cellular genes. 18,19 It is considered a mammalian homolog of the yeast Prp24 protein, and functions as a general pre-mRNA splicing factor.…”
Section: Introductionmentioning
confidence: 99%
“…12 Tat-interacting protein of 110 kDa (TIP110), which was initially cloned from a human KG-1 myeloid cell line cDNA library, 13 is implicated in RNA metabolism and tumor-antigen presentation. [14][15][16][17] We demonstrated previously that TIP110 regulates the transcription of HIV-1 and cellular genes. 18,19 It is considered a mammalian homolog of the yeast Prp24 protein, and functions as a general pre-mRNA splicing factor.…”
Section: Introductionmentioning
confidence: 99%
“…Specific antibodies against NUDC could be useful in inhibiting the growth of these carcinogenic cells [49]. hNUDC was also identified in cutaneous T-cell lymphoma by serological identification of antigens which have triggered the immunological response in tumor-bearing patients [50]. hNUDC has also been identified in a proteomic background study of esophageal cancer comparing tumor cells and the matched neighboring normal epithelial cells from surgical specimens.…”
Section: Functions Of Mammalian Nudcmentioning
confidence: 99%
“…Emerging evidence has indicated that NudC may be involved in carcinogenesis (Miller et al, 1999;Lin et al, 2004;Hatakeyama et al, 2006;Suzuki et al, 2007;Hartmann et al, 2008). NudC is highly expressed in early myeloid and erythroid precursors and declines as these cells terminally differentiate (Miller et al, 1999).…”
Section: Clinical Implication Of Nudc Familymentioning
confidence: 99%
“…A significant increase of NudC is observed in bone marrow aspirates from patients with acute lymphoblastic leukemia and acute myelogenous leukemia compared to that from normal donors, indicating that NudC may be associated with hematopoietic cell proliferation and leukemogenesis. NudC has also been identified as an up-regulated gene in cutaneous T-cell lymphoma (Hartmann et al, 2008). Interestingly, Hatakeyama et al find an inverse correlation between NudC expression levels and nodal metastasis in esophageal cancer by using a comprehensive and quantitative proteomic strategy (Hatakeyama et al, 2006).…”
Section: Clinical Implication Of Nudc Familymentioning
confidence: 99%